Linnaeus tercentenary and invertebrate taxonomy: an introduction* - Zhang, Zhi-Qiang; Shear, William A. (Zootaxa, 2007)
Carl Linnaeus (1707–1778) is the founding father of modern taxonomy. The binominal nomenclatural system for species and the principles of biological classification that he developed in the 18th century provide the basis on which we name and group organisms today. The tenth edition of his monumental Systema Naturae (Linnaeus 1758) marks the beginning of zoological nomenclature (ICZN 1999) and zoology as a modern branch of the natural sciences. Linnaeus’ genius was to see and understand what others had not: the requirement for a simple, easily applied, and consistent system of classification. That the fundamental principles of his work have survived two and a half centuries of repeated challenges stands as a tribute to that genius.